GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 100060 species occurrences available in GBIF matching the query: Country: Brazil Geometry: POLYGON((-58.57 -2.28,-58.57 5.17,-46.85 5.17,-46.85 -2.28,-58.57 -2.28)) HasGeospatialIssue: false. The dataset includes 100060 records from 257 constituent datasets: 2 records from UFMT - Herbário UFMT. 2 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 575 records from Field Museum of Natural History (Zoology) Mammal Collection. 5 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 31 records from UPCB - Herbário do Departamento de Botânica. 314 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 1 records from Mammal collection, Natural History Museum, University of Oslo. 9 records from CUMV Fish Collection (Arctos). 4 records from Homoptera. 47 records from Phanerogamic Botanical Collections (S). 484 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 627 records from MICROBIS database. 10 records from Bernice P. Bishop Museum. 1 records from Senckenberg - CeDAMar Resource. 12 records from UFP - Herbário UFP - Geraldo Mariz. 6 records from JPB - Herbário Lauro Pires Xavier. 8 records from Harvard University Herbaria. 1250 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4836 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Diplopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Mammal specimens. 67 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 14 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 8 records from Mammalogy Collection - Royal Ontario Museum. 13 records from Speothos Venaticus por Guillermo Gil. 5 records from MVZ Mammal Collection (Arctos). 4 records from Royal Botanic Garden Edinburgh Herbarium (E). 3569 records from Museum of Comparative Zoology, Harvard University. 3060 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 30 records from Snow Entomological Museum Collection. 17 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 4 records from HEPH - Herbário Ezechias Paulo Heringer. 2 records from Collection Ichthyologie - SNSD. 1 records from HUFU - Herbarium Uberlandense. 2 records from Collection Aves (spirit preserved) SMF. 9 records from Therevid PEET Project. 12 records from United States National Plant Germplasm System Collection. 3 records from CRI - Herbário Pe. Dr. Raulino Reitz. 2 records from CUMV Mammal Collection (Arctos). 1 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 5 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 10 records from Australian Museum provider for OZCAM. 1 records from The Lichen Collection at the Botanische Staatssammlung München. 38 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 1 records from SJRP-Pteridophyta - Herbário de Pteridophyta de São José do Rio Preto. 2 records from Collection Aves (bird skins) SMF. 4 records from CUMV Amphibian Collection (Arctos). 26 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 19 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 1 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 6 records from TEPB - Herbário Graziela Barroso. 69 records from Geneva Herbarium – General Collection (G). 2 records from Andes to Amazon Biodiversity Program. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 77 records from MAL. 887 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 23 records from Lichen herbarium, Oslo (O). 783 records from IAC - Herbário do Instituto Agronômico de Campinas. 11 records from LSUMZ Mammals Collection. 53 records from ICN - Herbário do Instituto de Ciências Naturais. 191 records from MAR - Herbário do Maranhão. 22 records from Geographic distribution of dinoflagellate cysts in surface sediments. 3 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 1 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 69 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 5 records from HRCB - Herbário Rioclarense. 11 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 34 records from Australia's Virtual Herbarium. 2 records from Invertebrate Zoology Division, Yale Peabody Museum. 2 records from MVZ Bird Collection (Arctos). 10 records from UCM Amphibian and Reptile Collection (Arctos). 17 records from Instituto de Ciencias Naturales. 1408 records from Insect Occurrence Data from MIZA. 2 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 25 records from Bee Biology and Systematics Laboratory. 4 records from Natural History Museum Rotterdam (NL) - Insecta collection. 46 records from A preliminary inventory of the catfishes of the lower Rio Nhamundá, Brazil (Ostariophysi, Siluriformes). 12 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 7 records from NCSM Invertebrates Collection. 2 records from Australian National Herbarium (CANB). 2 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 43 records from RBINS collections. 24 records from NRM-Herpetology. 1475 records from Naturalis Biodiversity Center (NL) - Botany. 183 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 32 records from CAS Botany (BOT). 3 records from Northern Territory Museum and Art Gallery provider for OZCAM. 31 records from Occurrences in SinBIOTA. 1 records from HST - Herbário Sérgio Tavares. 3 records from Collection Crustacea SMF. 4 records from Sand flies of Eastern Africa. 1 records from UMMZ Mammal Collection. 4 records from UFRN-Fungos - Herbário UFRN - Fungos. 13 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 154 records from Fishbase. 3 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 3 records from MEXU/Colección de Briofitas. 4 records from MBML-Herbario - Herbário Mello Leitão. 183 records from FURB - Herbário Dr. Roberto Miguel Klein. 1 records from CONN. 2 records from Harold W. Manter Laboratory of Parasitology Collection. 61 records from SPF - Herbário da Universidade de São Paulo. 26 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 94 records from Hymenoptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 64 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 1 records from Collection Arachnology SMF. 2 records from Lund Botanical Museum (LD). 9047 records from EOD - eBird Observation Dataset. 295 records from EAC - Herbário Prisco Bezerra. 9 records from SysTax - Zoological Collections. 6 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 6 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 163 records from UF FLMNH Ichthyology. 9 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 23 records from MBM - Herbário do Museu Botânico Municipal. 370 records from URM - Herbário Pe. Camille Torrand. 11 records from Coleção de Polychaeta do Museu Nacional. 38 records from Collection Pisces SMF. 6 records from ASE - Herbário da Universidade Federal de Sergipe. 1 records from MSB Host Collection (Arctos). 4 records from CESJ - Herbário Leopoldo Krieger. 54 records from Herbario Amazónico Colombiano. 4294 records from HAMAB - Herbário Amapaense. 3 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 1 records from Colección de Entomología - Heteroptera. 41 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 7 records from HDJF - Herbário Dendrológico Jeanine Felfili. 6 records from UFG - Herbário da Universidade Federal de Goiás. 5 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 3904 records from Missouri Botanical Garden. 1 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 11 records from MVZ Herp Collection (Arctos). 24 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 4 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2609 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 458 records from Paleobiology Database. 2 records from Hexacoral Database. 1 records from invertebratezoology. 55 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 208 records from SysTax - Herbaria. 26 records from PACA-AGP - Herbarium Anchieta. 25 records from KUBI Mammalogy Collection. 159 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 18 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 14978 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 3 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 4 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 1 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2329 records from NMNH occurrence DwC-A. 30 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 6 records from Myxozoa Collection - Instituto Nacional de Pesquisas da Amazônia. 148 records from NRM-Fishes. 5 records from Lichen Herbarium Berlin. 267 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 5 records from Herbarium Berolinense. 141 records from Illinois Natural History Survey Insect Collection. 113 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 117 records from CAS Herpetology (HERP). 1 records from Amblypygi Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16776 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 5412 records from Herbier de la Guyane. 10 records from Queensland Museum provider for OZCAM. 155 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 145 records from The System-wide Information Network for Genetic Resources (SINGER). 1 records from CNCR/Colección Nacional de Crustaceos. 9 records from Field Museum of Natural History (Botany) Fungi Collection. 1 records from AUM Fish Collection. 11 records from Herpetology Collection - Instituto Nacional de Pesquisas da Amazônia. 2287 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 33 records from Natural History Museum, Vienna - Herbarium W. 37 records from Colección de Entomología - Diptera - Ceratopogonidae. 1 records from CUMV Reptile Collection (Arctos). 4 records from South Australian Museum Australia provider for OZCAM. 104 records from CPAP - Herbário CPAP. 6 records from University of Vienna, Institute for Botany - Herbarium WU. 609 records from Field Museum of Natural History (Zoology) Fish Collection. 14 records from naturgucker. 2 records from Fish specimens. 580 records from UB - Herbário da Universidade de Brasília. 14 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 10 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 1 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 28 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 1 records from HURB - Herbário do Recôncavo da Bahia. 3 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from MOSS - Herbário Dárdano de Andrade Lima. 38 records from SINGER Coordinator. 79 records from NX - Herbário Nova Xavantina. 28 records from Tulane University Museum of Natural History. 11 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 12 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 8 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 1 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 47 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 109 records from UEC - Herbário da Universidade Estadual de Campinas. 1081 records from Mosquito Occurrence Dataset. 2 records from SAIAB: National Fish Collection (1880-2008). 8 records from Naturalis Biodiversity Center (NL) - Aves. 4 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from SOMBASE BIOCONSTRUCTORS. 457 records from Field Museum of Natural History (Zoology) Bird Collection. 1174 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 2 records from HPL - Herbário do Jardim Botânico Plantarum. 6 records from iNaturalist research-grade observations. 248 records from Macaulay Library Audio and Video Collection. 2 records from Orchid Herbarium Collection. 152 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 8 records from Ichthyology Collection - Royal Ontario Museum. 235 records from Entomology Division, Yale Peabody Museum. 183 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 3 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 1 records from Australian National Wildlife Collection provider for OZCAM. 3 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 245 records from SP-Fungi - Maria Eneyda Pacheco Kauffmann Fidalgo. 3 records from Field Museum of Natural History (Botany) Lichen Collection. 162 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 1246 records from CAS Ichthyology (ICH). 1075 records from Coleção de Abelhas do Departamento de Biologia - FFCLRP/USP. 31 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 1 records from Parasitic Platyhelminthes Collections. 24 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 23 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 991 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 5 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 32 records from R - Herbário do Museu Nacional. 1 records from SDNHM Herpetology Collection. 26 records from ALCB - Herbário Alexandre Leal Costa. 15 records from CM Herps Collection. 3 records from HERBAM - Herbário da Amazônia Meridional. 54 records from Opiliones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1878 records from KUBI Herpetology Collection. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 566 records from UMMZ Birds Collection. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 57 records from Natural History Museum (London) Collection Specimens. 185 records from AntWeb. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 23 records from Registros biológicos del género Piper en el herbario HUA. 13 records from iziko South African Museum - Shark Collection (AfrOBIS). 22 records from SLUI - Herbário Rosa Mochel. 8 records from FUEL - Herbário da Universidade Estadual de Londrina. 892 records from LACM Vertebrate Collection. 6 records from Global subterranean fishes. 1 records from The Fish Collection at the Zoologische Staatssammlung München. 20 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 1 records from Herbario Universidad de Antioquia (HUA). 2 records from Colección de Entomología - Hymenoptera - Parasitica. 8 records from Herbarium Senckenbergianum (FR). 17 records from KUBI Ichthyology Collection. 6 records from Naturalis Biodiversity Center (NL) - Mollusca. 8 records from NODC WOD01 Plankton Database. 343 records from Geographically tagged INSDC sequences.
Keywords: GBIF; biodiversity; species occurrences